Motivasi Kerja Generasi Z : Analisis Work-Life Balance dan Tantangan Stigma Generasi - Bayu Ade Prabowo; Yuniarto R. Satato; Mukhamad Kholil Aswan (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This research aims to analyze Generation Z work motivation in the context of work-life balance implementation and generational stigma challenges in Indonesian workplace settings, addressing the growing need to understand unique characteristics and expectations of this emerging workforce demographic. This study employed a mixed-method approach with sequential explanatory design, utilizing purposive sampling to collect data from 200 Generation Z employees (aged 18-28 years) across various industry sectors through structured questionnaires containing Likert scale measurements and open-ended questions. Quantitative data analysis used SPSS 26.0 including descriptive statistics, Pearson correlation, independent t-test, ANOVA, and multiple linear regression, while qualitative data underwent thematic analysis using NVivo 12 for coding and theme identification. Findings revealed that Generation Z work motivation is primarily driven by learning opportunities (M = 4.12) and career development rather than financial incentives, with work-life balance showing moderate implementation (M = 3.52) and significant positive correlation with work motivation (r = 0.675, p < 0.001). Generational stigma remains a concern (M = 3.41) with negative impact on work motivation (r = -0.523, p < 0.001), though most respondents employ adaptive strategies. Qualitative analysis identified four key satisfaction themes: learning and development (82%), supportive work environment (67%), flexibility (54%), and meaningful contribution (43%). Work-life balance and generational stigma collectively explain 61.2% of Generation Z work motivation variance, suggesting organizations need comprehensive strategies including flexibility policies, continuous development programs, and inter-generational bridging initiatives, with future longitudinal and cross-cultural studies recommended for deeper understanding.